Electrolyte additive for lithium ion battery and manufacturing method thereof
By using electrolytes containing lithium salts, phosphorus-containing additives and solvents in lithium-ion batteries, the capacity reduction and voltage reduction caused by phase change of lithium-manganese-rich materials at high voltage is solved, and the battery life and high voltage performance are achieved promote.
Patent Information
- Application Number
- CN202311482391.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-18
- Filing Date
- 2023-11-08
- Publication Date
- 2025-02-21
AI Technical Summary
Laminated oxide materials rich in lithium manganese are prone to phase change during the electrochemical cycle, resulting in a decrease in battery capacity and a decrease in operating voltage, especially at voltages above 4.3V.
Using an electrolyte containing lithium salt, phosphorus-containing additive and solvent, the lithium salt is present at 5 to 30% by weight and the phosphorus-containing additive is present at 0.001 to 20% by weight, to reduce the rate of conversion of the layered phase into spinel phase, and The cell expansion is reduced by forming an oxygen trap.
By reducing the rate at which the layered phase is converted into spinel phase, it extends the battery life, improves the decomposition temperature of the electrolyte, reduces the battery volume expansion, and improves the battery's high voltage performance.
Smart Images

Figure CN119495820A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to an electrolyte additive for a high voltage lithium battery and a method for making the same. Background Art
[0002] Lithium-ion batteries are traditionally used in various small commercial applications, such as tablets and laptops, mobile phones, etc. Recently, cathode active materials comprising lithium manganese-rich layered oxides, also known as lithium magnesium-rich (LMR) layered cathode materials, have been used due to their high energy density. The lithium manganese-rich layered oxide material contains a Li2MnO3 and LiR1O2 layered phase parent structure, where R1 is nickel. Lithium-ion batteries with lithium manganese-rich layered cathode materials show high reversible charge capacities of more than 200 milliampere-hours per gram mass (mAh / g). This makes them useful in various high-power applications, such as for automotive use.
[0003] Although these lithium-manganese-rich layered cathode materials have high specific capacities, the capacity of these materials is susceptible to rapid capacity degradation due to the evolution of the Li2MnO3 and LiR1O2 layered phase parent structures to the spinel phase during electrochemical cycling. This effect also leads to lower operating voltages, which compromises the energy density of the battery (commonly referred to as "voltage decay"). During the first charging cycle, this phase transition is known to occur at the surface of the electrode particles along with oxygen evolution as Li2O is lost from the Li2MnO3 parent structure. In subsequent cycles, the layered to spinel phase change continues from the particle shell to the core, accompanied by the evolution of Mn (Mn 2+ ) dissolution. Although the phase transition occurring in the first cycle can be considered an “activation” step, the long-term phase transition of lithium-manganese-rich layered oxide materials leads to a gradual decrease in the battery operating voltage and capacity, making the material unsuitable for lithium-ion batteries.
[0004] More specifically, these batteries suffer from a number of disadvantages when subjected to high voltage operation, greater than 4.3 volts (V). At voltages above 4.3 V, electrolyte decomposition occurs, resulting in undesirable oxygen release.
[0005] Therefore, it is desirable to provide high voltage performance in lithium-ion batteries. Summary of the invention
[0006] In one embodiment, an electrolyte for a lithium ion battery includes a lithium salt; a phosphorus-containing additive; and a solvent.
[0007] In another embodiment, the lithium salt is present in an amount of 5 to 30 wt %, based on the total weight of the electrolyte.
[0008] In yet another embodiment, the lithium salt is lithium hexafluorophosphate, lithium perchlorate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium bis(oxalate)borate, lithium difluoromethanesulfonyl)(trifluoromethanesulfonyl)imide, lithium difluorooxalatoborate, lithium difluorophosphate, lithium iodide, lithium bromide, lithium chloride, lithium thiocyanate, lithium nitrate, lithium nitrite, lithium sulfate, or a combination thereof.
[0009] In yet another embodiment, the lithium salt is lithium hexafluorophosphate (LiPF6).
[0010] In yet another embodiment, the phosphorus-containing additive is present in the electrolyte in an amount of 0.001 to 20 wt %, based on the total weight of the electrolyte.
[0011] In yet another embodiment, the phosphorus-containing additive is present in the electrolyte in an amount of 0.001 to 5 wt %, based on the total weight of the electrolyte.
[0012] In yet another embodiment, the phosphorus-containing additive is an organophosphite, an organophosphate, an organophosphonite, an organophosphonate, or a combination thereof.
[0013] In another embodiment, the organic phosphite and organic phosphonite are trimethyl phosphite, triethyl phosphite, triisopropyl phosphite, ethyl diphenyl phosphinate, triphenyl phosphite, tris(2,2,2-trifluoroethyl) phosphite, tris(1,1,1,3,3,3-hexafluoroprop-2-yl) phosphite, tris(trimethylsilyl) phosphite, or a combination thereof.
[0014] In another embodiment, the organophosphate is trimethyl phosphate, triphenyl phosphate, tributyl phosphate, triethyl phosphate, tris(2,2,2-trifluoroethyl) phosphate, di(2,2,2-trifluoroethyl) phosphate, tris(1,1,1,3,3,3-hexafluoroprop-2-yl) phosphate, or a combination thereof.
[0015] In another embodiment, the organic phosphonate is dimethyl methylphosphonate, diethyl ethylphosphonate, diethyl phenylphosphonate, bis(2,2,2-trifluoroethyl)methylphosphonate, bis(2,2,2-trifluoroethyl)methylphosphonate, or a combination thereof.
[0016] In yet another embodiment, the phosphorus-containing additive is tris(2,2,2-trifluoroethyl)phosphite.
[0017] In yet another embodiment, the solvent is diethyl carbonate, fluoroethylene carbonate, difluoroethylene carbonate, 1,2-dimethoxyethane, trifluoroethylene carbonate, vinyl vinyl carbonate, 4-methyleneethylene carbonate, propylene carbonate, vinylene carbonate, 4,5-dimethylene-1,3-dioxolane-2-one, dimethyl carbonate, ethyl methyl carbonate, 2,2,2-trifluoroethyl methyl carbonate, dimethyl sulfone, ethyl methyl sulfone, ethyl vinyl sulfone, tetramethylene sulfone, trifluoromethyl ethyl sulfone, trifluoromethyl isopropyl sulfone, trifluoropropyl methyl sulfone, vinyl sulfite, vinyl sulfate, dimethyl sulfoxide, acetonitrile, N,N-dimethylformamide, water, or a combination thereof.
[0018] In yet another embodiment, the solvent comprises diethyl carbonate and fluoroethylene carbonate.
[0019] In yet another embodiment, the amount of diethyl carbonate used is 75 to 85 volume % based on the total weight of the solvent used in the electrolyte, wherein the amount of fluoroethylene carbonate used is 15 to 25 volume % based on the total volume of the solvent used in the electrolyte.
[0020] In one embodiment, a lithium ion battery includes an anode, a cathode, an electrolyte and a separator. The anode includes an anode active layer. The cathode includes a cathode active layer, wherein the cathode active layer includes a layered structure material rich in lithium and manganese. The electrolyte includes a phosphorus-containing additive. The separator is disposed between the anode and the cathode.
[0021] In another embodiment, the electrolyte further includes a lithium salt; wherein the lithium salt is lithium hexafluorophosphate, lithium perchlorate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium bis(oxalate)borate, lithium bis(difluoromethanesulfonyl)(trifluoromethanesulfonyl)imide, lithium difluorooxalatoborate, lithium difluorophosphate, lithium iodide, lithium bromide, lithium chloride, lithium thiocyanate, lithium nitrate, lithium nitrite, lithium sulfate, or a combination thereof.
[0022] In yet another embodiment, the lithium and manganese rich layered structure material has a chemical formula of formula (1) or formula (2):
[0023] (p)Li2MnO3(1-p)LiR1O2(1),
[0024] wherein R1 is Mn, Ni or Co, and p is greater than 0 and less than 1;
[0025] R x M y O2(2),
[0026] Wherein, R is Ni, M is at least one of Mn, Ni, Co or Al, x+y=1, and x is greater than 0.30 and less than 0.91.
[0027] In yet another embodiment, the lithium- and manganese-rich layered structure material is Li z Ni x Mn y Co (1-x-y) O2、LiNi x Mn y Al (1-x-y) O2、LiNi x Mn (1-x) O2 or a combination thereof, or a combination thereof, wherein y is equal to or greater than about 0.5, x is less than 0.4, and z is equal to or greater than 1.0 and less than 1.5.
[0028] In yet another embodiment, the phosphorus-containing additive reduces the rate at which the layered phase in the lithium- and manganese-rich layered structure material transforms into the spinel phase.
[0029] In yet another embodiment, the phosphorus-containing additive is tris(2,2,2-trifluoroethyl)phosphite.
[0030] The above features and advantages and other features and advantages of the present disclosure will become apparent from the following detailed description when taken in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Other features, advantages and details appear, by way of example only, in the following detailed description, which refers to the accompanying drawings, in which:
[0032] Figure 1 is a schematic diagram of an exemplary lithium-ion battery;
[0033] Figure 2 is a schematic diagram of the reaction between the phosphorus-containing additive and oxygen, which results in the removal of oxygen generated in the battery;
[0034] Figure 3 It describes the area capacity (mAh / cm2) of the experimental battery and the comparison battery. 2 ) versus cycle number; and
[0035] Figure 4 is a graph depicting the normalized capacity retention versus cycle number for the experimental and comparative cells. DETAILED DESCRIPTION
[0036] The following description is merely exemplary in nature and is not intended to limit the present disclosure, its application, or uses.
[0037] According to an exemplary embodiment, a lithium ion battery comprising an electrolyte is disclosed herein, the electrolyte comprising a phosphorus-containing additive. The lithium ion battery also includes a cathode having a cathode active material layer, the cathode active material layer comprising a layered structure material rich in lithium and manganese (LMR). The use of an electrolyte comprising a phosphorus-containing additive reduces the phase transition of the cathode active layer from a layered phase to a spinel phase, thereby increasing the life of the battery. The phosphorus-containing additive also promotes the formation of a cathode-electrolyte interface (CEI), sometimes also referred to as a solid electrolyte interface (SEI) of the anode, which acts as an oxygen trap to reduce battery volume expansion. The phosphorus-containing additive helps to improve stability, thereby increasing the decomposition temperature of the electrolyte. This improves battery life.
[0038] Figure 1 A cross section of an exemplary lithium ion battery 100 is depicted, which includes an anode 120 and a cathode 120 contained in a housing 200, which also includes a separator 108 and an electrolyte 106. The anode includes an anode current collector 102 having an anode active material layer 104 disposed thereon, and the cathode includes a cathode active material layer 110 disposed on a cathode current collector 112. Various components of the battery 100 are contained in the housing 200, which includes terminals 202 and 204, which are typically in electrical communication with a load (not shown).
[0039] Anode active material layer 104 and cathode active material layer 110 are generally manufactured by respectively disposing anode active material layer and cathode active material layer on anode current collector 102 and cathode current collector 112. Liquid electrolyte 106 surrounds anode 120 and cathode 130. Separator 108 generally comprises an electrically insulating material and is disposed between anode 120 and cathode 130.
[0040] Anode current collector 102 and cathode current collector 112 typically comprise metal. In one embodiment, the anode current collector comprises stainless steel, copper, nickel, iron, titanium, or a combination thereof, and the cathode current collector comprises stainless steel, aluminum, nickel, iron, titanium, or a combination thereof.
[0041] The electrolyte 106 will be described first, followed by descriptions of electrode (anode and cathode) active material layers, materials used in the respective active material layers, methods of manufacturing the respective electrodes, and methods of manufacturing the battery 100 .
[0042] The electrolyte 106 used in lithium-ion batteries includes a lithium salt, a phosphorus-containing additive, and a solvent. It is desirable that the lithium salt completely dissolves and dissociates in the electrolyte, and that the solvated lithium ions (Li +) should have high mobility for ion transport. The anion should be stable to oxidative decomposition at the cathode and reductive decomposition at the anode. Examples of lithium salts include lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium tetrafluoroborate (LiBF4), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(oxalate)borate (LiBOB), lithium bis(difluoromethanesulfonyl)(trifluoromethanesulfonyl)imide (LiDFTFSI), lithium difluorooxalatoborate (LIODFB), lithium difluorophosphate (LiPO2F2), lithium iodide (LiI), lithium bromide (LiBr), lithium chloride (LiCl), lithium thiocyanate (LiSCN), lithium nitrate (LiNO3), lithium nitrite (LiNO2), lithium sulfate (Li2SO4), or a combination thereof.
[0043] The lithium salt is present in the electrolyte in an amount of 5 to 30 weight percent (wt %) based on the total weight of the electrolyte.
[0044] The electrolyte 106 also includes a phosphorus-containing additive that reduces electrolyte decomposition and oxygen generated by the decomposition. In one embodiment, the phosphorus-containing additive may include at least one of fluorine, silicon, or a combination thereof. The fluorine or silicon in the phosphorus-containing additive may be covalently or ionically bonded to the phosphorus atom directly or indirectly. The phosphorus-containing additive acts as an oxygen trap to reduce battery volume expansion.
[0045] Figure 2 An exemplary interaction mechanism of phosphorus-containing additives with oxygen, which helps remove oxygen generated in the battery, is depicted in FIG. Figure 2 An exemplary reaction of a phosphite molecule (e.g., hydrogen phosphate or acidic phosphite) with oxygen to form a phosphate is described. The reaction with oxygen molecules to form a phosphate helps remove oxygen generated in the battery, thereby preventing battery expansion and geometric deformation.
[0046] Examples of phosphorus-containing additives that can be used in the electrolyte include phosphites, phosphinates, phosphonates, phosphates, or combinations thereof. In one embodiment, the phosphorus-containing additive includes an organic phosphite, an organic phosphate, an organic phosphonite, an organic phosphonate, or a combination thereof.
[0047] Examples of organic phosphites and organic phosphonites include trimethyl phosphite (TMPi), triethyl phosphite, triisopropyl phosphite, ethyl diphenyl phosphite, triphenyl phosphite (TEPi), tris(2,2,2-trifluoroethyl) phosphite, tris(1,1,1,3,3,3-hexafluoroprop-2-yl) phosphite, tris(trimethylsilyl) phosphite, and the like, or combinations thereof.
[0048] Examples of suitable organic phosphates include trimethyl phosphate (TMPa), triphenyl phosphate, tributyl phosphate, triethyl phosphate, tris(2,2,2-trifluoroethyl) phosphate, di(2,2,2-trifluoroethyl) phosphate, tris(1,1,1,3,3,3-hexafluoroprop-2-yl) phosphate, and the like, or combinations thereof.
[0049] Examples of suitable organic phosphonates include dimethyl methylphosphonate, diethyl ethylphosphonate, diethyl phenylphosphonate, bis(2,2,2-trifluoroethyl)methylphosphonate, bis(2,2,2-trifluoroethyl)methylphosphonate, and the like, or combinations thereof.
[0050] Combinations of any of the foregoing phosphorus-containing additives may be used. For example, the phosphorus-containing additive may include an organic phosphate and an organic phosphite. A preferred phosphorus-containing additive is tris(2,2,2-trifluoroethyl)phosphite.
[0051] The phosphorus-containing additive may be present in the electrolyte in an amount of 0.001 to 20 wt %, preferably 0.01 to 10 wt %, more preferably 0.1 to 5 wt %, based on the total weight of the electrolyte.
[0052] The electrolyte 106 contains a solvent that dissolves the lithium salt and the phosphorus-containing additive. The solvent should facilitate ion migration. Examples of suitable solvents include diethyl carbonate (DEC), fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), 1,2-dimethoxyethane (DME), trifluoroethylene carbonate (TFEC), vinyl ethylene carbonate (VEC), 4-methylene ethylene carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), vinylene carbonate (VC), 4,5-dimethylene-1,3-dioxolane-2-one, dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), 2,2,2-trifluoroethyl methyl carbonate (MFEC), dimethyl sulfone (DMS), ethyl methyl sulfone (EMS), ethyl vinyl sulfone (EVS), tetramethylene sulfone (TMS), trifluoromethyl ethyl sulfone (FMES), trifluoromethyl isopropyl sulfone (FMIS), trifluoropropyl methyl sulfone (FPMS), vinyl sulfite, vinyl sulfate, dimethyl sulfoxide (DMSO), acetonitrile, N,N-dimethylformamide (DMF), water, and the like, or a combination thereof.
[0053] A co-solvent may also be used. In one embodiment, water may be used to dissolve the lithium salt before mixing with one or more solvents. When a co-solvent is used, the amount of the first solvent may be 10 to 90 volume percent (volume %), preferably 20 to 80 volume %, based on the total volume of the solvent used in the electrolyte. The amount of the second solvent may also be 10 to 90 volume %, preferably 20 to 80 volume %, based on the total volume of the solvent used in the electrolyte.
[0054] Suitable cosolvent system comprises diethyl carbonate and fluoroethylene carbonate.When diethyl carbonate and fluoroethylene carbonate were used in the cosolvent system, based on the gross weight of solvent for use in the electrolyte, the consumption of diethyl carbonate can be 10-90 volume %, preferably 15-85 volume %, preferably 75-85 volume %.Based on the gross weight of solvent for use in the electrolyte, the consumption of fluoroethylene carbonate can also be 10 to 90 volume %, preferably 15 to 85 volume %, preferably 15 to 25 volume %.
[0055] The electrolyte 106 is prepared by mixing an appropriate amount of a lithium salt, a phosphorus-containing additive, and a solvent to form a solution. The mixing is performed in a blender in which shear forces are applied to the components. Suitable blenders include Waring blenders, Henschel blenders, planetary blenders, and single-screw or twin-screw extruders. If desired, the mixing can be performed at ambient temperature and pressure, or at high temperature and pressure. In a preferred embodiment, the mixing is performed at ambient temperature and pressure. When desired, the electrolyte 106 is disposed in the battery housing 200.
[0056] The manufacture of the electrode (anode 120 or cathode 130) will now be described. In one embodiment, the slurry used to form the electrode includes a solvent, a conductive additive, a polymer binder, an active material (the active material can be an anode active material or a cathode active material, depending on which specific electrode (anode or cathode) it is used for).
[0057] The solvents used to make the anode active layer 104 and the cathode active layer 110 may be the same as the solvents listed above, and for the sake of brevity, they will not be described in detail.
[0058] The conductive additive preferably includes a conductive carbonaceous material. Examples of conductive carbonaceous materials include carbon nanotubes, carbon black, activated carbon, graphene, graphite, graphite oxide, carbon fibers, etc. or combinations thereof. It is desirable that the conductive composition forms a conductive network extending from the current collector surface to the electrode surface (contacting the electrolyte).
[0059] Carbon nanotubes include single-walled carbon nanotubes (SWNT), double-walled carbon nanotubes (DWNT), multi-walled carbon nanotubes (MWNT) or combinations thereof, and have a diameter of 2 to 100 nanometers, preferably 10 to 50 nanometers. Their length is 20 to 10,000 nanometers, preferably 200 to 5,000 nanometers. An aspect ratio greater than 10, preferably greater than 50, more preferably greater than 100 is desirable.
[0060] Carbon black with a high surface area is preferred for electrodes. Carbon black (subtypes are acetylene black, channel black, furnace black, lamp black, and thermal black) is a material produced by the incomplete combustion of coal and coal tar, vegetable matter, or petroleum products (including fuel oil, fluid catalytic cracking tar, and ethylene cracking) under limited air supply. Carbon black is a subcrystalline carbon with a high surface area to volume ratio, although lower than that of activated carbon. The surface area is 50 to 1000 m 2 / gm of carbon black may be used in the slurry for forming the electrode.
[0061] Activated carbon, also known as activated carbon, is a carbon with a surface area of more than 3000m 2 / gm of carbon. It can be used in combination with other conductive carbonaceous elements listed here. An example of carbon black or activated carbon that can be used in the electrode forming slurry is Keltjen TM Black or Super P.
[0062] Graphene is an allotrope of carbon consisting of a single layer of atoms arranged in a hexagonal lattice nanostructure. The graphene added to the slurry can be in the form of a single graphene sheet or multiple loosely connected graphene sheets. Each atom in the graphene sheet is connected to the three nearest atoms via σ-bonds and delocalized π-bonds, which contribute to the formation of a valence band that extends throughout the sheet. This is the same type of bonding found in carbon nanotubes and polycyclic aromatic hydrocarbons, fullerenes, and glassy carbon. The conduction band touches the valence band, making graphene a semimetal with unusual electronic properties that are best described by theories of massless relativistic particles.
[0063] In one embodiment, the graphene may be in the form of graphene nanoplatelets (GNPs). Expanded graphite nanoplatelets include nanoparticles containing graphite. These nanoparticles are composed of small stacks of graphene 1 to 15 nanometers thick, with diameters ranging from submicron to 100 microns.
[0064] Graphite particles can also be used in conductive compositions. Graphite is a natural manifestation of pure carbon with a hexagonal crystal structure arranged in multiple parallel layers, called graphene layers. In simple terms, a graphite particle consists of multiple graphene sheets arranged parallel to each other. This anisotropic structure gives graphite special properties, such as electrical conductivity or special strength along the layers. It is very heat-resistant, with a sublimation point of over 3800°C, high thermal conductivity and chemical inertness.
[0065] Graphite oxide (GO), sometimes called graphene oxide, graphite oxide, or graphitic acid, is a compound of variable ratios of carbon, oxygen, and hydrogen obtained by treating graphite with strong oxidants and acids to decompose additional metals. The most oxidized bulk product is a yellow solid with a C:O ratio between 2.1:1 and 2.9:1, retaining the lamellar structure of graphite but with much larger irregular spacing. The bulk material disperses spontaneously in alkaline solutions or can be dispersed ultrasonically in polar solvents to produce monomolecular sheets, similar to graphene in the form of single-layer graphite, called graphene oxide. Graphene oxide sheets exist in the form of strong paper-like materials, films, thin films, and composites, and can be used in electrode-forming slurries for preparing electrodes.
[0066] Carbon fibers have a diameter of 5 to 10 micrometers and are primarily composed of carbon atoms. They may have a length greater than 1000 micrometers, preferably greater than 10,000 micrometers. They are produced by stretching pitch or polyacrylonitrile polymer fibers at high pressure and temperature exceeding 1500°C, preferably at a temperature greater than 2200°C. Carbon fibers are different from carbon nanotubes and do not have concentrically arranged cylindrical graphene sheets. Carbon fibers generally include high aspect ratio graphene sheets arranged parallel to each other.
[0067] The aforementioned carbon nanotubes, carbon black, activated carbon, graphene sheets, graphite particles, graphite oxide particles or combinations thereof may be used alone or in any combination to form a conductive network. In an exemplary embodiment, carbon nanotubes are generally used in the largest amount compared to other carbon-containing components.
[0068] The active layer may contain up to 5% by weight, preferably 1 to 4% by weight, of conductive additives, based on the total weight of the active layer.
[0069] The electrode forming slurry may also optionally include a polymer binder. The polymer binder binds the conductive additive and the active material so that they remain in contact with the current collector and are not dispersed in the electrolyte during the manufacturing process or use. The polymer binder preferably does not reduce the conductivity of the active layer disposed on the current collector. The active layer includes a conductive additive and a corresponding anode or cathode active material.
[0070] The polymer binder is preferably a fluorine-containing homopolymer or copolymer. In a preferred embodiment, the binder is a fluorine-containing copolymer. In one embodiment, the fluorine-containing copolymer is poly (vinylidene fluoride-chlorotrifluoroethylene) (abbreviated as P (VDF-CTFE)), poly (vinylidene fluoride-trifluoroethylene) (abbreviated as P (VDF-TeFE)), poly (vinylidene fluoride-trifluoroethylene-chlorofluoroethylene) terpolymer (abbreviated as P (VDF-TrFE-CFE)), poly (vinylidene fluoride-hexafluoropropylene) (abbreviated as P (VDF-HFP) or PVDF-HFP) at least one, or a combination thereof. In a preferred embodiment, the polymer binder used in the active layer is a poly (vinylidene fluoride-hexafluoropropylene) copolymer. The weight average molecular weight of the polymer binder is 5000 to 1000000 grams per mole, preferably 50000 to 750000 grams per mole, more preferably 75000 to 500000 grams per mole, measured using gel permeation chromatography with polystyrene standards.
[0071] In one embodiment, the polyvinylidene fluoride content of any of the foregoing binders is 80 to 95% by weight based on the total weight of the polymer binder. The remaining polymer content of the copolymer is 5 to 20% by weight based on the total weight of the polymer binder. For example, if the polymer binder is a poly(vinylidene fluoride-hexafluoropropylene) copolymer, the polyvinylidene fluoride content of the copolymer is 80 to 95% by weight based on the total weight of the polymer binder, and the polyhexafluoropropylene content of the copolymer is 5 to 20% by weight based on the total weight of the copolymer.
[0072] After removing the solvent, the total weight of the polymer binder in the active layer is less than 10 weight percent of the total weight of the active layer, preferably less than 8 weight percent, more preferably less than 5 weight percent, and more preferably less than 3 weight percent. If a polymer binder is present, it is present in an amount greater than 0.1 weight percent of the total weight of the active layer. A lower weight of polymer binder in the active layer is conducive to a lower reduction in the electrical conductivity of the active layer. In other words, the lower the amount of polymer binder, the greater the electrical conductivity of the active layer. The active layer is disposed on a current collector and includes an associated (anode or cathode) active material, a conductive additive, and a polymer binder.
[0073] The electrode forming slurry contains an active material. The active material may be different depending on whether the slurry is used to form an anode active layer or a cathode active layer.
[0074] Anode active materials include some of the above carbonaceous materials, hard carbon, silicon, silicon mixed with graphite, silicon oxide mixed with graphite, carbon encapsulated silicon particles, Li4Ti5O 12; transition metals such as tin, metal oxides, metal sulfides (e.g., TiO2, FeS, etc.), lithium metal and alloys, or combinations thereof. Exemplary active materials may include graphite, hard carbon, activated carbon, carbon in nanoform, silicon, silicon oxide, silicon oxide mixed with graphite, carbon-encapsulated silicon nanoparticles, or combinations thereof. In some such embodiments, the anode active material may be intercalated with lithium (e.g., using pre-lithiation methods known in the art).
[0075] Hard carbon is a solid form of carbon that cannot be converted into graphite by heat treatment, even at temperatures as high as 3000°C. It is also called charcoal, or non-graphitizable carbon. Hard carbon is produced by heating a carbon-containing precursor to about 1000°C in the absence of oxygen. The precursors of hard carbon are polyvinylidene chloride (PVDC), lignin, and sucrose. Other precursors, such as polyvinyl chloride (PVC) and petroleum coke, produce soft carbon, or graphitizable carbon. Soft carbon can be easily converted into graphite by heating to 3000°C.
[0076] In a preferred embodiment, the anode active material comprises silicon oxide mixed with graphite.The anode active material may be used in the anode active layer in an amount of 3 to 99 wt %, preferably 4 to 60 wt %, based on the total weight of the anode active layer.
[0077] Layered structure materials rich in lithium (Li) and manganese (LMR) can be used as cathode active materials. Layered oxides rich in lithium manganese (LMR), also known as overlithiated oxides (OLO), have attracted attention as cathode materials for lithium-ion batteries due to their high capacity (greater than 250 mAh / g) and energy density. The following formula (1) provides an example of LMR:
[0078] (p)Li2MnO3(1-p)LiR1O2(1),
[0079] Wherein, R1 is Mn, Ni or Co, and p is greater than 0 and less than 1.
[0080] Another example of LMR is provided in equation (2) below:
[0081] R x M y O2(2),
[0082] Wherein, R is Ni, M is at least one of Mn, Ni, Co or Al, x+y<1, and x is greater than 0.1 and less than 0.5.
[0083] An example of an LMR is Li[Li 1 / 3 Mn 2 / 3]O2 (commonly known as Li2MnO3) and LiR1O2 (where R1 is nickel), which have a specific capacity of about 250 mAh / g. Other LMRs that can be used for the cathode active layer include lithium manganese oxide (LMO, with variations of LiMn2O4, Li2MnO3 and other compounds), LiNbO3-coated LiMn2O4 and Al-doped LiMn2O4.
[0084] Examples of other LMRs include lithium cobalt oxide (LCO, sometimes called "lithium cobaltate" or "lithium cobalt oxide" - a variant of which is LiCoO2); lithium nickel manganese cobalt oxide (NMC, with a variant formula of LiNiMnCo); lithium nickel cobalt aluminum oxide (LiNiCoAlO2 and variants such as NCA); and lithium titanate oxide (LTO, with a variant formula of Li4Ti5O 12 ); lithium iron phosphate oxide (LFP, a variant of which is LiFePO4), lithium nickel cobalt aluminum oxide (and its variant NCA) and other similar materials, spinel (LiMn2O4, LiNi 0.5 Mn 1.5 O4), polyanion cathodes (LiV2(PO4)3), and other lithium transition metal oxides. Low voltage cathode materials such as lithiated metal oxides / sulfides (e.g., LiTiS2), lithium sulfide, and sulfur can also be used.
[0085] Other variations of the foregoing may be included. In some embodiments using NMC as the active material, a nickel-rich NMC may be used. For example, in some embodiments, a variation of NMC may be LiNi x Mn y Co (1-x-y) O2、LiNi x Mn y Al (1-x-y) O2、LiNi x Mn (1-x) O2、Li 1+x MO2 or a combination thereof, wherein x is equal to or greater than about 0.7, 0.75, 0.80, 0.85 or greater, and wherein y is less than 0.15, preferably less than 0.1. In some embodiments, NMC811 may be used, wherein in the foregoing formula, x is about 0.8 and y is about 0.1.
[0086] In yet another embodiment, the lithium- and manganese-rich layered structure material is Li z Ni x Mn y Co (1-x-y) O2、LiNi x Mn y Al (1-x-y) O2、LiNi xMn (1-x) O2 or a combination thereof, wherein y is equal to or greater than about 0.5, x is less than 0.4, and z is equal to or greater than 1.0 and less than 1.5.
[0087] The cathode active materials may be used in the cathode active layer in an amount of 70 to 99 wt %, preferably 95 to 98 wt %, based on the total weight of the cathode active layer, respectively.
[0088] Electrode forming slurry can be manufactured in a variety of different ways. In one embodiment, in a method of manufacturing each electrode (anode or cathode), a conductive composition, a polymer binder, an anode or cathode active material and a solvent (such as those listed above) can be mixed in a single mixing device such as a stirrer for a suitable time to form a slurry. The mixing time can be 30 minutes to 5 hours. Then the slurry with the appropriate active material is placed on each current collector to form an anode or cathode. The slurry placed on the current collector is dried to form an active layer.
[0089] Drying can be carried out at a temperature of 50 to 80°C for 30 minutes to 10 hours, preferably 1 to 5 hours. Mixing is carried out in a planetary mixer, although other mixers such as Waring mixers, Henschel mixers, single screw and multi-screw extruders can also be used.
[0090] In one embodiment, the battery 100 is manufactured by placing an anode 120 (which includes an anode current collector 102 and an anode active layer 104 disposed thereon), a cathode 130 (which includes a cathode current collector 112 disposed thereon and a cathode active layer 110), a separator 108, and an electrolyte 106 (with a phosphorus-containing additive) in a casing 200. The casing 200 is sealed. The battery is then provided with an anode terminal 202 (contacting one or more anodes) and a cathode terminal 204 (contacting one or more cathodes).
[0091] The N / P ratio of a lithium-ion battery is the capacity ratio between the positive and negative electrodes of the battery. The capacity ratio is usually the area capacity. It is used to determine battery performance and energy density. In one embodiment, the N / P ratio is controlled by adjusting the anode thickness with a fixed anode density. In another embodiment, the battery has an N / P ratio of 1 to 3, preferably 1.1 to 1.5, and more preferably 1.1 to 1.2. An N / P ratio greater than 1.10 can inhibit lithium plating and enhance cycle performance. N / P ratios between 1.15 and 1.40 can also show good discharge capacity.
[0092] A battery comprising the aforementioned anode active layer, cathode active layer and electrolyte having a phosphorus-containing additive can be operated at a C-rate of C / 100 to 6C in a voltage range of 2.0 to 5.0 volts. The C-rate is a measure of how fast a battery can be charged or discharged. It is defined as the current (amperes) divided by the capacity (ampere-hours). For example, if the battery has a capacity of 100 ampere-hours and can be charged at a rate of 10 amperes, the C-rate is 10 / 100, or 0.1.
[0093] Batteries having the foregoing electrolytes are illustrated by the following non-limiting examples.
[0094] Example
[0095] This example was conducted to demonstrate the functionality of a lithium ion battery comprising a phosphorus-containing additive as part of the electrolyte. The phosphorus-containing additive used in this example was tris(2,2,2-trifluoroethyl)phosphite (abbreviated as TTFPi).
[0096] Two lithium batteries were tested in this example, one was an experimental battery containing an electrolyte containing a phosphorus-containing additive, and the other was a control battery containing an electrolyte without a phosphorus-containing additive. The components and fabrication of each battery cell are described in detail below.
[0097] The electrolytes of both lithium-ion batteries contain LiPF6 as its lithium salt. A 1.2M solution of LiPF6 was mixed with a co-solvent solution of fluoroethylene carbonate (FEC) and diethyl carbonate (DEC). The volume ratio of FEC to DEC was 1:4. Tris(2,2,2-trifluoroethyl)phosphite (TTFPi) was added to the electrolyte of the experimental battery in an amount of only 3 wt % based on the total weight of the electrolyte. The control battery did not contain any tris(2,2,2-trifluoroethyl)phosphite (TTFPi) in its electrolyte and therefore contained only a 1.2M solution of LiPF6 in a co-solvent solution of fluoroethylene carbonate (FEC) and diethyl carbonate (DEC) in a volume ratio of 1:4.
[0098] The anode active layer and cathode active layer of both (experimental and comparative) lithium-ion cells were identical and are described in detail below.
[0099] The anode active layer comprises a mixture of silicon dioxide and graphite (SiO / graphite) as the anode active material. Based on the total weight of the anode active layer, the anode active material is present in the anode active layer in an amount of 5.5 wt%. The anode active layer used in this embodiment comprises 95 wt% of active material, the active material comprising a combination of graphite and silicon dioxide bonded to graphite (the amount of SiO-C is 5.5 wt%), 3.9 wt% of a binder, the binder comprising carboxymethyl cellulose and styrene-butadiene rubber in a weight ratio of 1:1 and 1.1 wt% of Super-P carbon black.
[0100] The cathode active layer includes a layered cathode active material rich in lithium magnesium (LMR). The anode active layer includes 97 wt % LMR, 0.1 wt % single-walled carbon nanotubes, 1.05 wt % Super-P carbon black, 0.6 wt % graphene nanosheets (GNPs) and 1.25 wt % of a polymer binder including polyvinylidene fluoride. All weight percentages are based on the total weight of the cathode active layer.
[0101] The cells were cycled at C / 3 between 2 and 4.4 V. Formation was performed at C / 20 between 2.0 and 4.5 V. The C-rate (C) is defined as the charge / discharge current divided by the nominal rated cell capacity; here 1 C = 200 mA / g.
[0102] The performance of these two lithium batteries is Figure 3 and Figure 4 A comparison was made in . Figure 3 is the area capacity (mAh / cm2) of the experimental cell (depicted by numeral 300) and the comparative cell (depicted by numeral 400). 2 )(600) versus the number of cycles (500), and Figure 4 is a graph depicting the percent normalized capacity retention (700) versus cycle number (500) for an experimental cell (depicted by numeral 300) and a comparative cell (depicted by numeral 400).
[0103] from Figure 3 It can be seen that the areal capacity of the experimental cell containing the phosphorus-containing additive is greater than that of the control cell. This areal capacity increases with the number of cycles, indicating that the life cycle of the cell can be improved by using an electrolyte containing the phosphorus-containing additive. Similarly, from Figure 4 It can be seen that the normalized capacity retention of the experimental cell is greater than that of the control cell with increasing cycle number. Both examples demonstrate the utility of using phosphorus-containing additives in the electrolyte. Phosphorus-containing additives help reduce the conversion rate of the layered phase to the spinel phase in the layered structure material rich in lithium and manganese.
[0104] The terms "one" and "an" do not indicate a limitation of quantity, but rather indicate the presence of at least one of the referenced items. The term "or" means "and / or", unless the context clearly indicates otherwise. References to "an aspect" throughout the specification mean that a particular element (e.g., feature, structure, step, or characteristic) described in conjunction with that aspect is included in at least one aspect described herein, and may or may not be present in other aspects. In addition, it should be understood that the described elements may be combined in any suitable manner in various aspects.
[0105] When an element such as a layer, film, region, or substrate is referred to as being “on” another element, it can be directly on the other element or intervening elements may also be present. In contrast, when an element is referred to as being “directly on” another element, there are no intervening elements present.
[0106] Unless otherwise indicated herein, all test standards are the most recent standards in effect as of the filing date of the present application or, if priority is claimed, the filing date of the earliest priority application in which the test standards appear.
[0107] Unless defined otherwise, technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure belongs.
[0108] Although the above disclosure has been described with reference to exemplary embodiments, it will be appreciated by those skilled in the art that various changes may be made and equivalents may be substituted for its elements without departing from the scope thereof. In addition, many modifications may be made to adapt specific situations or materials to the teachings of the disclosure without departing from the essential scope of the disclosure. Therefore, it is intended that the disclosure is not limited to the specific embodiments disclosed, but will include all embodiments falling within its scope.
Claims
1. An electrolyte for a lithium ion battery, comprising: Lithium salts; Phosphorus-containing additives; as well as Solvent.
2. The electrolyte according to claim 1, wherein The lithium salt is present in an amount of 5 to 30 wt % based on the total weight of the electrolyte, and wherein the lithium salt is lithium hexafluorophosphate.
3. The electrolyte according to claim 1, wherein The phosphorus-containing additive is present in the electrolyte in an amount of 0.001 to 20 wt % based on the total weight of the electrolyte, and wherein the phosphorus-containing additive is an organic phosphite, an organic phosphate, an organic phosphonite, an organic phosphonate, or a combination thereof.
4. The electrolyte according to claim 3, wherein The organic phosphites and organic phosphonites are trimethyl phosphite, triethyl phosphite, triisopropyl phosphite, ethyl diphenylphosphinate, triphenyl phosphite, tris(2,2,2-trifluoroethyl) phosphite, tris(1,1,1,3,3,3-hexafluoroprop-2-yl) phosphite, tris(trimethylsilyl) phosphite or a combination thereof; wherein the organic phosphate is trimethyl phosphate, triphenyl phosphate, tributyl phosphate, triethyl phosphate, tris(2,2,2-trifluoroethyl) phosphate, di(2,2,2-trifluoroethyl) phosphate, tris(1,1,1,3,3,3-hexafluoroprop-2-yl) phosphate or a combination thereof; and wherein the organic phosphonate is dimethyl methylphosphonate, diethyl ethylphosphonate, diethyl phenylphosphonate, bis(2,2,2-trifluoroethyl) methylphosphonate, bis(2,2,2-trifluoroethyl) methylphosphonate or a combination thereof.
5. The electrolyte according to claim 1, wherein The phosphorus-containing additive is tris(2,2,2-trifluoroethyl)phosphite.
6. The electrolyte according to claim 1, wherein The solvent is diethyl carbonate, fluoroethylene carbonate, difluoroethylene carbonate, 1,2-dimethoxyethane, trifluoroethylene carbonate, vinylethylene carbonate, 4-methyleneethylene carbonate, propylene carbonate, vinylene carbonate, 4,5-dimethylene-1,3-dioxolane-2-one, dimethyl carbonate, ethyl methyl carbonate, 2,2,2-trifluoroethyl methyl carbonate, dimethyl sulfone, ethyl methyl sulfone, ethyl vinyl sulfone, tetramethylene sulfone, trifluoromethyl ethyl sulfone, trifluoromethyl isopropyl sulfone, trifluoropropyl methyl sulfone, vinyl sulfite, vinyl sulfate, dimethyl sulfoxide, acetonitrile, N,N-dimethylformamide, water or a combination thereof.
7. The electrolyte according to claim 1, wherein The solvents include diethyl carbonate and fluoroethylene carbonate.
8. The electrolyte according to claim 7, wherein The diethyl carbonate is used in an amount of 75 to 85 volume % based on the total weight of the solvent used in the electrolyte, and the fluoroethylene carbonate is used in an amount of 15 to 25 volume % based on the total volume of the solvent used in the electrolyte.
9. A lithium ion battery comprising: an anode including an anode active layer; a cathode comprising a cathode active layer; wherein the cathode active layer comprises a layered structure material rich in lithium and manganese; an electrolyte comprising a phosphorus-containing additive; and A separator is disposed between the anode and the cathode.
10. The battery according to claim 9, wherein The electrolyte further comprises a lithium salt; wherein the lithium salt is lithium hexafluorophosphate, lithium perchlorate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium bis(oxalate)borate, lithium bis(difluoromethanesulfonyl)(trifluoromethanesulfonyl)imide, lithium difluorooxalatoborate, lithium difluorophosphate, lithium iodide, lithium bromide, lithium chloride, lithium thiocyanate, lithium nitrate, lithium nitrite, lithium sulfate or a combination thereof, and wherein the phosphorus-containing additive is tris(2,2,2-trifluoroethyl)phosphite.